2022
DOI: 10.1590/0074-02760210302
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii in the faeces of wild felids from the Atlantic Forest, Brazil

Abstract: BACKGROUND Toxoplasma gondii is a apicomplexan parasite of virtually all warm-blooded species. All true cats (Felidae) can act as definitive hosts for this parasite by shedding resistant oocysts into the environment. However, the patterns of oocysts shedding are only partially understood in domestic cats and largely unknown in wild felids.OBJECTIVES We carried out molecular analysis of 82 faecal samples from wild felids collected in the Serra dos Órgãos National Park (Parnaso), Rio de Janeiro, Brazil.METHODS W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Given the short patent period of T. gondii infections in felines (1-2 weeks following primary infection) [46], it is rare to find oocysts in fecal samples from these hosts. The low prevalence of positive fecal samples for oocysts found in this study (5%, 1/20, in wildcats) is similar to other studies on wild felines, including red lynx (Lynx rufus) (6.2%; 1/16) and cougars (Puma concolor) (1.9%; 1/52) in North America [8], jaguars (Puma yagouaroundi) (1.22%; 1/82) in a regional park in Brazil [47], and wildcats (F. silvestris) from Greece (1.6-4.3%) [48]. Oocysts can be difficult to differentiate from those of Hammondia hammondi and Besnoitia spp.…”
Section: Discussionsupporting
confidence: 89%
“…Given the short patent period of T. gondii infections in felines (1-2 weeks following primary infection) [46], it is rare to find oocysts in fecal samples from these hosts. The low prevalence of positive fecal samples for oocysts found in this study (5%, 1/20, in wildcats) is similar to other studies on wild felines, including red lynx (Lynx rufus) (6.2%; 1/16) and cougars (Puma concolor) (1.9%; 1/52) in North America [8], jaguars (Puma yagouaroundi) (1.22%; 1/82) in a regional park in Brazil [47], and wildcats (F. silvestris) from Greece (1.6-4.3%) [48]. Oocysts can be difficult to differentiate from those of Hammondia hammondi and Besnoitia spp.…”
Section: Discussionsupporting
confidence: 89%
“…With the presence of the Type II lineage and now the Africa 4 lineage, the diversity in South Africa may be similar to that observed in North and East Africa, even though the Type III lineage described in these regions has not yet been found in South Africa (Galal et al, 2018;Lachkhem et al, 2021). A recent study showed that T. gondii lineages from the Old World (Africa, Asia and Europe), including the Africa 4 lineage, would be better adapted to the domestic environment, with a better potential for the sexual reproduction efficiency of these strains in the domestic cat (Galal et al, 2022). This is not incompatible with the identification of what is called domestic strain in a wild host such as the Black-backed Jackal, given the proximity between the wild and domestic environments in South Africa.…”
Section: Discussionmentioning
confidence: 67%
“…This is not incompatible with the identification of what is called domestic strain in a wild host such as the Black-backed Jackal, given the proximity between the wild and domestic environments in South Africa. The presence of domestic cats as a potential source of oocysts capable of disseminating into the wild environment has also been proposed in previous studies in North and South America (Jiang et al, 2018;Bolais et al, 2022).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations